2016
DOI: 10.1007/s00280-016-3010-1
|View full text |Cite
|
Sign up to set email alerts
|

A first-in-Asian phase 1 study to evaluate safety, pharmacokinetics and clinical activity of VS-6063, a focal adhesion kinase (FAK) inhibitor in Japanese patients with advanced solid tumors

Abstract: Purpose VS-6063 (also known as defactinib or PF-04554878) is a second-generation inhibitor of focal adhesion kinase and proline-rich tyrosine kinase-2. This phase 1 study evaluated the safety and tolerability, pharmacokinetics, and clinical activity of VS-6063 in Japanese subjects with advanced solid tumor malignancies in a first-in-Asian study setting.MethodsVS-6063 was administered orally twice daily (b.i.d.) in 21-day cycles to cohorts of three subjects each with a standard 3 + 3 dose-escalation design unti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(61 citation statements)
references
References 22 publications
3
57
0
Order By: Relevance
“…Finally, the 8q24 region is the most commonly amplified genomic region in SOC, containing MYC and FAK. Inhibitors to FAK, such as defactinib, are already being tested in the clinic [116], and will hopefully provide some positive results in the near future.…”
Section: Potential For New Treatments By Targeting Copy Number Alteramentioning
confidence: 99%
“…Finally, the 8q24 region is the most commonly amplified genomic region in SOC, containing MYC and FAK. Inhibitors to FAK, such as defactinib, are already being tested in the clinic [116], and will hopefully provide some positive results in the near future.…”
Section: Potential For New Treatments By Targeting Copy Number Alteramentioning
confidence: 99%
“…Pre-clinical models demonstrated that maintenance therapy with defactinib delayed tumor regrowth in MPM patient derived xenograft models (126). In a phase I study, one patient with MPM was reported to have radiographic stable disease while on defactinib for 24 weeks at a dose of 400 mg (127). Interestingly, another phase I study with a different FAK inhibitor, GSK2256098, reported that MPM patients with documented loss of Merlin had increased median PFS at 23.4 weeks (n=14) compared to MPM patients with preserved Merlin expression who had median PFS at 11.4 weeks (n=9) (128).…”
Section: Focal Adhesion Kinase (Fak) Inhibitorsmentioning
confidence: 99%
“…Α recent study has previously reported the high expression and prognostic value of Cd26 in malignant mesothelioma (17,18), humanized anti-Cd26 monoclonal antibody, yS-110, having inhibitory effect on malignant mesothelioma cell growth in vitro and in vivo experiments (19), and one of the promising new developments for the antibody-based treatment of mesothelioma (19,20). Other trials such as pembrolizumab against programmed death 1 (Pd-1) antibody, PF-03446962 against activin receptor-like kinase 1 (ALK-1), defactinib against focal adhesion kinase (FAK) are ongoing (21)(22)(23).…”
Section: No Of Invading Cells/ One Quadrant Of Insert --------------mentioning
confidence: 99%